New type of generalized difference sequence of fuzzy numbers involving lacunary sequences - Et, Mikail; Braha, Naim L.; Altinok, Hifsi (Ios Press, 2015)
In this paper, we introduce a new type of almost statistical convergence of generalized difference sequences of fuzzy numbers involving lacunary sequences. We give the relations between the lacunary strongly almost Cesaro type convergence and lacunary almost statistical convergence. Furthermore, we study some of their properties like completeness, solidity, symmetricity etc. We also give some inclusion relations related to these classes.
Keywords: Almost statistical convergence; difference sequence; fuzzy numbers; solidness; symmetricity; convergence free